The potency of Temu Mango Rhizome Extract (Curcuma mangga Valeton & Zijp) at Variation of Solvent Concentration as Sunscreen - Susiloningrum, Dwi; Mugitasari, Dessy Erliani (Biomedika, 2022)
Human skin has a natural protection system against the harmful effects of sunlight by thickening the stratum, corneum, and skin pigmentation. Some plants are known to have benefits that can be used as natural ingredients to protect the skin from the adverse effects of sunlight. Plants that have secondary metabolites as sunscreen activity are temu mango rhizome (Curcuma mangga Valeton & Zijp). Secondary metabolite compounds contained in the mango meeting include flavonoid compounds, phenolics, tannins, essential oils which are known to function as sunscreens. This study aims to determine the SPF value of temu mango rhizome (Curcuma mangga Valeton & Zijp) using various solvents, namely ethanol 50%, 70%, and 96%. Calculation of the SPF value using the Mansur method. The results showed that the SPF value produced by the 50% ethanol extract of temu mango rhizome (Curcuma mangga Valeton & Zijp) with concentrations of 1250 ppm, 2500 ppm, 3750 ppm, 5000 ppm were 9.0613; 12,4133; 10.6027; 17,1233 with an SPF value of 12,3001 including the category of maximum protection. The SPF value produced by the 70% ethanol extract of temu mango (Curcuma mangga Valeton & Zijp) with the same concentration was 14.1767, respectively; 13.4787; 17,699; 17.4507 with an SPF value of 15.7013 including the ultra protection category. The SPF values ​​produced by the 96% ethanol extract of temu mango rhizome (Curcuma mangga Valeton & Zijp) with the same concentration were 14,892, respectively; 17.3617; 16.9197; 16,972 with an SPF value of 16,5363 including ultra protection category.